(untitled) (International Journal of Environmental Sciences, 2025)
The use of 3D printing technology has completely changed how drugs are delivered. It is now used in oral controlled-release systems, transdermal patches, implants, microneedles, rapidly dissolving tablets, and dosage forms that release drugs in multiple phases. This technology has a lot of benefits over traditional methods. For example, it can make personalised medications with complex structures, specific drug release characteristics, and faster small-batch production while wasting less material. Even though it has medical and economic benefits, technical and regulatory issues are making it hard for it to be widely used in pharmaceuticals right now. This review explores various 3D printing techniques and their applications in drug delivery, further discussing the technological and regulatory challenges and proposed solutions to facilitate personalised healthcare and customised pharmaceuticals.